The White‐sand Vegetation of Acre, Brazil. (18th January 2016) - Daly, Douglas C.; Silveira, Marcos; Medeiros, Herison; Castro, Wendeson; Obermüller, Flávio A.
Abstract: For vegetation on white sand in Amazonia, the topography, soil nutrients, level of the water table, and rainfall combine to result in distinct formations, each with a characteristic physiognomy and each with a rather distinct floristic composition and very distinct dominants. We describe the physiognomies and present the floristic composition of nine formations, based on intensive fieldwork in NW Acre state, Brazil, where on six sites we have documented 222 species; 170 of them are woody plants or trunked palms ≥5 cm diam. Herbaceous species are good indicators for some of the formations. Distribution patterns and habitat specialization can be difficult to interpret because they often require familiarity with the localities and local terminologies involved. Many of the species show disjunct distributions congruent with the occurrence of other white‐sand areas in northern South America. The nine formations within Acre are strongly dissimilar, with only two pairwise comparisons showing >50 percent similarity. Comparison of the Acre white‐sand flora with datasets from Peruvian and Central + Eastern Amazonia show striking differences in composition and in taxonomic dominance, with more than 95 percent dissimilarity. White‐sand formations in Acre and elsewhere are gravely affected by expanding human settlement; little is known about the regeneration and recovery of the degraded white‐sand habitats. This complex sector of Acre's biological diversity is still virtually unrepresented in conservation units anywhere in Brazil's part of southwestern Amazonia, so it should be made an immediate conservation priority.